(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
Skinner sistematically described mentalism as an obstacle to the resolution of human problems. According to him, the adoption of this explanatory model hides accessible and manipulable critical variables, which are responsible for the production and for the maintenance of social problems, specially the behavioural ones. This paper presents a real case where this mentalistic explanatory model was used by the Brazilian Minister of Justice in order to understand a complex behavioural phenomenon (violence) and how the adoption of this model conducted to a particular kind of public policy of intervention (increase of conscience in the population). The concepts of violence and conscience were discussed using behavioral-analytic theoretical instrumental contrasting diagnose and indicated solutions by each theoretical alternative.